A new type of transforming growth factor-beta, TGF-beta 3. - Derynck, R (1988)
A new type of TGF-beta, TGF-beta 3, has been identified by cDNA characterization. The amino acid sequence of mature TGF-beta 3 and its precursor has been derived from porcine and human cDNA sequences. The human TGF-beta 3 gene is spread over seven exons as in the case of the TGF-beta 1 gene. Comparison with TGF-beta 1 and -beta 2 indicates a strong conservation of the mature sequences, but a relaxed homology in the precursor segments. TGF-beta 3 mRNA is mainly expressed in cell lines from mesenchymal origin, suggesting a biological role different from the other TGFs-beta.